Does African American Race Impact Statin Efficacy in Renal Transplant Outcomes?. Issue 49 (December 2015) - Ozieh, Mukoso N.; Taber, David J.; Egede, Leonard E.
Abstract : Abstract: There is a lack of studies assessing if race impacts the efficacy of 3-hydroxy-3-methyl-glutaryl-CoA reductase (HMGCR) inhibitor ("statin") therapy on renal transplantation (RTx) outcomes. We examined the association between statin therapy and RTx outcomes, while concurrently quantifying the effect modification African American (AA) race has on statin efficacy. This was a retrospective longitudinal cohort study of solitary adult RTx (n = 1176) between June 2005 and May 2013. The Cox proportional hazard model was used to examine the impact of statin therapy on graft loss, death, and acute rejection and determine if significant interactions exist between statin therapy and race. Models were adjusted for demographics, socioeconomic status, cardiovascular history, medication use, and transplant characteristics. AAs (n = 624) and non-African Americans (n = 552) were equally likely to receive statin therapy ( P = 0.922). Mean LDL and TGs in AA were 94 mg/dL and 133 mg/dL compared to 90 mg/dL and 163 mg/dL in non-AA, respectively. After adjusting for confounders, high statin users had 52% lower risk of developing graft loss (HR 0.48, 95% CI 0.29–0.80) and a nonstatistically significant reduction in death (HR 0.50, 95% CI 0.23–1.06) compared to low statin users. Acute rejection was not significantly influenced by statin use (HR 0.77 95% CI 0.46–1.27). There was a significant interaction between race and statin therapy for death ( P = 0.007), but not for graft loss ( P = 0.121) or rejection ( P = 0.605). After stratifying by race, high statin use reduced the risk of death in AAs (HR 0.43, 95% CI 0.20–0.94), but not in non-AAs (HR 1.09, 95% CI 0.49–2.44). High statin use reduces the risk of graft loss in RTx, with a mortality benefit in AAs compared to non-AA, despite similar LDL levels. These results suggest a compelling reason to optimize statin therapy in renal transplant recipients (RTR), especially in AAs.